Compaction Behavior of Co-Amorphous Systems - Cecilie-Mathilde Sørensen; Jukka Rantanen; Holger Grohganz (MDPI AG, 2023)
Co-amorphous systems have been shown to be a promising strategy to address the poor water solubility of many drug candidates. However, little is known about the effect of downstream processing-induced stress on these systems. The aim of this study is to investigate the compaction properties of co-amorphous materials and their solid-state stability upon compaction. Model systems of co-amorphous materials consisting of carvedilol and the two co-formers aspartic acid and tryptophan were produced via spray drying. The solid state of matter was characterized using XRPD, DSC, and SEM. Co-amorphous tablets were produced with a compaction simulator, using varying amounts of MCC in the range of 24 to 95.5% (w/w) as a filler, and showed high compressibility. Higher contents of co-amorphous material led to an increase in the disintegration time; however, the tensile strength remained rather constant at around 3.8 MPa. No indication of recrystallization of the co-amorphous systems was observed. This study found that co-amorphous systems are able to deform plastically under pressure and form mechanically stable tablets.